Diagnostic value of cancer markers CEA, AFP, cathepsin D and cancer procoagulant (CP) in patients with lung and oesophagus cancer - Kiluk, Marek; Wiśniewski, Ryszard; Dariusz Szajda, Sławomir; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2002)
Neoplastic markers used in oncological diagnosis are useful in detection and determination of clinical stages of cancer and radicalism of operative procedure and in monitoring of therapy. Until now it is little known about the possibility of using such markers as cathepsin D and cancer procoagulant in oncological diagnosis. The aim of the study was to measure and evaluate the clinical utility of the concentration of canceroembrionic antigen (CEA) and alpha-fetoprotein and activity of cathepsin D in serum of patients with lung and oesophagus cancer before radiotherapy, however 6 weeks and 2 months after the preliminary determination of cancer procoagulant activity was carried out. Examinations were carried out on serum obtained from 30 patients with lung planoepitheliale cancer and 16 patients with oesophagus planoepitheliale cancer in III a-b clinical stages (according to generally accepted classification - TNM) before radiotherapy, 6 weeks and 2 months after radiotherapy. Blood was taken from the elbow vein in the typical way and CEA, CFP, cathepsin D and procoagulant determination were determined in the obtained serum. CEA and AFP markers were determined by IMX Abbot analyzator. Activity of cathepsin D was determined by Folin-Ciocalteau method. Cancer procoagulant activity was examined by the coagulation method of Gordon and Benson. Results of the examination show that CEA concentration in cases of lung and oesophageal cancer was more than twice times higher before radiotherapy in comparison to control values. However 6 weeks after the treatment the CEA concentration was significantly decreased and two months after radiotherapy reached normal values. The examinations demonstrate that determination of CEA concentration in lung and oesophageal cancer is of great importance in cancer detection and in monitoring of cancer therapy. The high activity of cancer procoagulant in the blood serum of patients with lung and oesophageal cancer before treatment in comparison to control group was also shown. That is why cancer procoagulant should be regarded as a biochemical noeplastic marker, which may have a considerable significance in detecting of neoplastic disease. However, determination of AFP concentration and cathepsin D activity in lung and oesophageal cancer is diagnostically not useful, since the values of these markers do not significantly differ from the normal values.